Pengaruh Pemberian Aroma Terapi Lemon (Citrus Limon Per ) Terhadap Penurunan Emesis Gravidarum (Mual Dan Muntah) Pada Ibu Hamil Trimester Pertama Di Puskesmas Ciputat Jakarta Selatan Tahun 2023 - Dessy Ratna Sari Sembiring (Jurnal Ventilator, 2023)
Nausea and vomiting are symptoms that a reasonable and often happen in the first trimester of pregnancy. It usually occurs in the morning, but can occurs at any time including at night. This condition can cause dehydration or lack of fluid and electrolyte inbalance, hence the condition of pregnant mother's get worse. Lemon aromatherapy is one of alternative method to decrease nausea and vomiting in the first trimester of pregnancy. It provides relaxation and sedative by stimulating the limbic system. This study was conducted to find the effect of lemon aromatherapy to decrease nausea and vomiting in the first trimester of pregnancy. Design used in this study was pre-experiment (one-group pretest-posttest designed). The population were all pregnant women that have nausea and vomiting in the first trimester of pregnancy. The samples were 12 respondent taken by purposive sampling according to the inclusion criteria. The independent variable was lemon aromatherapy. While the dependent variables were nausea and vomiting in the first trimester of pregnancy. Data were collected using structured questionnaire and observation. Data were then analyzed using statistic test (wilcoxon signed rank test) with level of significance ??0.05. The result showed that giving lemon aromatherapy had an effect to decrease nausea and vomiting in the first trimester of pregnancy (p=0.002). There were differences of nausea and vomiting between pre-treatment lemon aromatherapy (x=8.50) and post-treatment lemon aromatherapy (x=4.25). It can be concluded that giving lemon aromatherapy could decreased nausea and vomiting in the first trimester of pregnancy. Lemon aromatherapy is useful to breathe when experiencing morning sickness, for relief, encouraging, refreshing, and improving mood, giving a relaxed feeling, comfortable and quiet. Recommendation for the nurse and other health profession to use lemon aromatherapy as alternative medication of nausea and vomiting in pregnant women.